2008
DOI: 10.1086/592360
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Employment‐Based Programs on Families by Prior Levels of Disadvantage

Abstract: This study examines how welfare and employment policies affect subpopulations of low-income families that have different levels of initial disadvantage. Education, prior earnings, and welfare receipt are used to measure disadvantage. The analysis of data from experiments suggests that employment-based programs have no effects on economic well-being among the least-disadvantaged low-income, single-parent families, but they have positive effects on employment and income for the most-disadvantaged and moderately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Studies reported no significant differences between intervention groups on adult depressive symptoms although depression again moderated the economic impacts in the SSP (51). Some new subgroup findings emerged including higher risk of depression among the most disadvantaged mothers compared to moderately disadvantaged mothers (53). …”
Section: Results: Policy Overviews and Health Impactsmentioning
confidence: 99%
“…Studies reported no significant differences between intervention groups on adult depressive symptoms although depression again moderated the economic impacts in the SSP (51). Some new subgroup findings emerged including higher risk of depression among the most disadvantaged mothers compared to moderately disadvantaged mothers (53). …”
Section: Results: Policy Overviews and Health Impactsmentioning
confidence: 99%
“…Prior level of disadvantage was also consequential. Pooling data from several of the state experiments mentioned above, Alderson, Gennetian, Dowsett, Imes, and Huston (2008) found that employment‐based programs had no significant effects on children's achievement and behavior for the most disadvantaged subgroup of respondents (measured in terms of prior earnings, education, and AFDC receipt), despite the fact that their mothers saw gains in employment, earnings, and household income. Children in the moderately disadvantaged groups, whose mothers enjoyed similar gains, however, achieved more in school.…”
Section: Families In Poverty In the Context Of Welfare Reformmentioning
confidence: 99%
“…Indeed, it is likely that changes in income have stronger effects on children in low-income families, who may be more vulnerable to material deprivation and stress (Alderson, Gennetian, Dowsett, Imes, & Huston, 2008). A study by Dearing, McCartney, and Taylor (2006) provides some evidence for this hypothesis.…”
Section: The Effects Of Income On the Development Of Low-income Childrenmentioning
confidence: 99%